Angone Bovine Growth Pattern Assessed by Nonlinear Models - Valdmiro Júlio Setâ; Fiodósia Henriques Álvaro; Baltazar do Azarento Isabel Chipiringo; Fernando Dos Santos Magaço (Universitas Tidar, 2022)
The study of the development and growth of cattle from birth to slaughter allows the identification of early individuals. The objective of this study were to identify the non-linear model with the best fit to describe the growth curve of Angone cattle. Data of live weights measurements in the range from birth to 720 days of age of 47 animals were used. The evaluated non-linear models were Gompertz, Von Bertalanffy, Logistic and Brody. The model fitness was compared using the: coefficient of determination, adjusted coefficient of determination, Akaike and Bayesian information criteria and mean square error as statistical criteria, and biological criteria the instantaneous growth rate and inflection point. Higher asymptotic weight (A) was observed for the Brody model (157.5 kg) and inverse behavior was observed for the maturing rate (K) with values ranging from 0.002 kg/day to 0.005 kg/day, demonstrating lower precocity of the evaluated group. Behavior supported by the instantaneous growth rate where gains of 0.030 kg/day were observed for the Gompertz model, 0.100 kg/day for the Logistic model, 0.127 kg/day for the Brody model and 0.168 kg/day for the Von Bertalanffy model. The Brody model provides better goodness of fit.